The Cultural Identity Construction of Temples for Tourism - Prabnok, Puttharak (European Journal of Social Science Education and Research, 2020)
This study presents Buddhist temples’ cultural identify construction to serve a tourism purpose in Thailand. Qualitative data were collected by in-depth interviews with 20 key informants who represented the temples and the tourism organizations. Research findings: The Buddhist temples, which are considered to be the main religious organization, had changed their role to fit the new social trend. In the past, temples were the heart of community lifestyles and the center of religious activity practice. In this present time, however, Buddhist temples become religious tourist places. Carrying such new role, it appears that temples have been trying to establish five cultural identifies with the aim to best serve the tourism. Those five cultural identities are increasing cultural capital value, capturing the tourists’ faith through the presentation of respected monk or abbot, combining Buddhist beliefs to the local faiths, setting up the temple’ tourism landmark, and building a unique tradition of the temple and the community.